2020
DOI: 10.1038/s41598-020-59201-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of floating riverine macro-debris transport using an image processing approach

Abstract: A new algorithm has been developed to quantify floating macro-debris transport on river surfaces that consists of three fundamental techniques: (1) generating a difference image of the colour difference between the debris and surrounding water in the CIELuv colour space, (2) detecting the debris pixels from the difference image, and (3) calculating the debris area flux via the template matching method. Debris pixels were accurately detected from the images taken of the laboratory channel and river water surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 51 publications
(39 reference statements)
0
26
0
Order By: Relevance
“…To date, the transport of macroplastic debris has been quantified using detection of plastic particles from aerial photographs taken by a drone from low heights (5 and 15 m; [35]). Macroplastic debris transport was also measured by visual counting from bridges, video approaches, trackers, net sampling, or from infrastructure or riverbanks (e.g., [13,18,26,27,40,56]). In future works, more details may be determined using a combination of a visual counting method with hydrodynamic modelling [57].…”
Section: Macroplastic Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the transport of macroplastic debris has been quantified using detection of plastic particles from aerial photographs taken by a drone from low heights (5 and 15 m; [35]). Macroplastic debris transport was also measured by visual counting from bridges, video approaches, trackers, net sampling, or from infrastructure or riverbanks (e.g., [13,18,26,27,40,56]). In future works, more details may be determined using a combination of a visual counting method with hydrodynamic modelling [57].…”
Section: Macroplastic Transportmentioning
confidence: 99%
“…Similar to the transport phase, the output phase may also be temporarily modified by hydropeaking or sediment flushing events occurring downstream from dams. The intensity of an output phase may be measured in the same way as for the transport phase (e.g., [27,40,56]). Finally, it can be also hypothesized that a proportion of surface-stored macroplastic debris may be transported by wind outside the storage/remobilization zone, hence being removed from the area potentially influenced by fluvial processes (Table 1).…”
Section: Macroplastic Outputmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, a method of measuring MacP during flooding, when various types of suspended matter flow downstream, has not been established. In order to solve such problems, Kataoka and Nihei [55] have proposed a MacP survey method that combines video image captures and image analyses of the river water surfaces, along with safety considerations. In the future, it will be essential to collect MacP concentration data using these methods to improve the accuracy of plastic emissions evaluations.…”
Section: Total Plastic Input From the Land To The Seamentioning
confidence: 99%
“…New technological advances can facilitate the upscaling of data collection across time (long-term time series) and space (more rivers, and more locations along single rivers). For example, Geraeds et al (2019) and Kataoka and Nihei (2020) demonstrated the potential of using Unmanned Aerial Vehicles (UAVs) and cameras to measure floating plastic and plastic on banks in river systems.…”
Section: Introductionmentioning
confidence: 99%